Pengaruh Pendapatan, Perilaku Keuangan dan Locus Of Control terhadap Pengambilan Keputusan Investasi pada Guru PNS SD di Kecamatan Buleleng - Prashanti, Ni Putu Berliana Gita; Astawa, I Gede Putu Banu (Vokasi : Jurnal Riset Akuntansi, 2021)
This study aims to determine the effect of income, financial behavior, and locus of control on the investment decision making of PNS SD teachers in Buleleng District. This research is a type of quantitative research with a total of 217 respondensts. The data were obtained by distributing questionnaires aimed at elementary school civil servant teachers in Buleleng District. Samples were selected using criteria with purposive sampling technique. The data used is primary data in the form of answers from respondents and processed using SPSS 15.0 for Windowns. The results of this study indicate that income has a significant effect on investment decision making for PNS SD teachers in Buleleng District, financial behavior has a significant effect on investment decision making for PNS SD teachers in Buleleng District, and locus of control has a significant effect on investment decision making for PNS SD teachers in Buleleng District.